Evaluation of the use of essential oils of cinnamon, oregano and eucalyptus in drinking water for broilers (Research, Society and Development, 2021)
The restriction use of antimicrobials as growth promoters in the production of broiler chickens has proven to be a major challenge. The use of alternative molecules, which have antimicrobial properties, aims to replace these drugs. Essential oils are molecules with great potential to replace growth promoters. The objective of this trial was to evaluate the use of essential oils derived from Eucalyptus globulus, Cinnamomum zeylanicus and Origanum vulgare via drinking water for broiler chickens. 450 COBB male chicks were used, distributed by experimental design, consisting of four treatments consisting of six replicates, with 15 animals in each replicate. The experiment consisted of negative control, positive control (2ppm flavomycin via feed), cinnamon oil + oregano (300 ml/1000L), and eucalyptus oil (300 ml/1000L). Differences were observed in zootechnical performance (p0.05), as well as the intestinal histomorphometric parameters (P>0.05). It concluded that the essential oils were able to replace flavomycin as a growth promoter, ensuring adequate zootechnical performance and without affecting the animals' health.